Effect of Bimanual Activities on Hand and Proprioception in Autism Spectrum Disorder (Indian Journal of Public Health Research & Development, 2021)
Background: Autism spectrum disorder (ASD) is defined as neurological and developmental disorder withcharacteristic features that include delayed gross motor milestones. It can be recognized at the initial stageduring infancy or childhood with major affection see in communication and behavioral response of the child.Every 1 child amongst 100 children suffers from autism in India. The aim of our study was to see the effectsof bimanual exercises on the hand function and kinesthetic awareness in the child with autism spectrumdisorder and the objective of the study was to measure kinesthetic awareness, to measure pegboard reactiontime and to measure grip strength.Method: 20 children were selected on the basis of inclusion and exclusion criteria and were divided into2 groups, interventional group (group A) and control group (group B), each group consisted of 10 childreneach. Group A has 6 boys and 4 girls and group B has 7 boys and 3 girls. A written consent was taken fromthe parent (guide) of autistic child and study was explained to them and data was collected and analyzedusing SPSS within the confidence interval of 95%. Result: - On the basis of data analysis table no. 1 showsthe prevalence of both the genders. And table no. 8 shows the comparison between interventional group andcontrol group within the confidence interval of 95% (with significant p value- 0.02)Conclusion: Bimanual exercises has been shown to be effective in improving hand function and kinestheticawareness in children suffering from Autism spectrum disorder.
Keywords: Autism Spectrum Disorder, Bimanual Activities, Hand Function, Pegboard Reaction Time, Grip Strength, Joint Position.